2020
DOI: 10.1097/md.0000000000021971
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal morphine versus local infiltration analgesia for pain control in total knee and hip arthroplasty

Abstract: Background: The purpose of this meta-analysis was to comprehensively collect randomized controlled trials (RCTs) to assess the clinical efficacy of intrathecal morphine (ITM) versus local infiltration analgesia (LIA) in the treatment of total knee and hip arthroplasty patients. Methods: Relevant studies were identified from the Embase, PubMed, Cochrane Library, Web of Science, Wanfang, and Chinese National Knowledge Infrastructure (CNKI) databases. We also reviewed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The incidence of nausea and pruritis was significantly higher in the ITM group, even though the overall opioid consumption was similar in both groups. Our trial results remain in line with a metanalysis which showed an associated increased pruritis and a decreased patient satisfaction [ 26 , 27 ], although no difference in side effect profile was observed in one study [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of nausea and pruritis was significantly higher in the ITM group, even though the overall opioid consumption was similar in both groups. Our trial results remain in line with a metanalysis which showed an associated increased pruritis and a decreased patient satisfaction [ 26 , 27 ], although no difference in side effect profile was observed in one study [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…In all studies, intrathecal morphine was associated with increased pruritus and decreased patient satisfaction. In a more recent meta-analysis, 87 intrathecal morphine was compared with LIA in both TKA and THA. The four RCTs in TKA patients showed no differences in postoperative analgesia and opioid-sparing with intrathecal morphine (100 to 300 μg) 91–94 .…”
Section: Resultsmentioning
confidence: 99%
“…[73][74][75][76][77][78][79][80][81][82][83][84] Three meta-analyses including four RCTs compared intrathecal morphine with FNB 85,86 and with LIA. 87 The dose of intrathecal morphine varied between 100 and 300 mcg (Table S1, http://links.lww.com/EJA/ A701). Compared with single shot FNB, there was no clinically significant difference in postoperative pain at rest or during mobilisation and no postoperative opioidsparing effect.…”
Section: Intrathecal Morphinementioning
confidence: 99%
“…The concept of administering local anaesthetics with opioid adjuncts via the intrathecal or epidural route is longstanding [33,34] and systematic reviews show this reduces the intrathecal local anaesthetic dose requirement [35] and prolongs analgesia in patients undergoing caesarean delivery [36][37][38] or lower limb arthroplasty [39,40]. Recent studies that compare intrathecal morphine with local infiltration analgesia for lower limb joint arthroplasty may change this practice, as local infiltration provides superior analgesia, reduces postoperative morphine consumption, shortens hospital stay and reduces morphine-related adverse effects [41,42].…”
Section: Anaesthetic Adjunctsmentioning
confidence: 99%